Methods to evaluate dietary intake of hospitalized patients. Validation of a plate diagram sheet for estimation of energy and protein intake of inpatients - Rannveig Björnsdóttir 1961- (2012)
Background & aims: Validation of simple methods for estimating energy and protein intakes in hospital wards are rarly reported in the literature. The aim was to validate a plate diagram sheet for estimation of energy and protein intakes of patients by comparison with weighed food records. Methods: Subjects were inpatients at the Cardio Thoracic ward, Landspitali National University Hospital, Reykjavik, Iceland (N=81). The ward personnel recorded the proportion (0%, 25%, 50%, 100%) of main meals (breakfast, lunch and dinner) and snack (afternoon- and evening snack) consumed for three days using a plate diagram sheet. The nutrition composition of the meals provided by the hospital kitchen is known and leftover food was weighed by a trained research person during the registration days. Energy and protein intake estimated by the plate diagram sheet was compared with the results from the weighed records by paired t-test. Pearson correlation was used to assess associations between the two methods. The overall agreement for energy- and protein intakes between the methods was assessed by Bland Altman plot and the limits of agreement computed (average difference ± 1.96 standard deviation of the difference). Results: On average the plate diagram sheet overestimated energy intake by 45 kcal/day (1119±353 kcal/day versus 1074±360 kcal/day, p=0.008). Estimation of protein intake was not significantly different between the two methods (50.2±16.4 g/day versus 48.7±17.7 g/day, p=0.123). If only meals were included where ≤50% of the meals served was consumed according to the plate diagram recording, a slight underestimation of the real consumption was observed. Correlation between the two methods was r = 0.922, p < 0.001 for energy intake (kcal/day) and r = 0.896, p < 0.001 for protein intake (g/day). According to Bland Altman the limits of agreement between the two methods for energy intake were -231 kcal/day to 322 kcal/day and for protein intake -14.0 g/day to 16.9 g/day. Conclusion: The results show that a plate ...